Horizontal and vertical emissions of carbon dioxide and methane from a tropical peat soil cultivated with pineapple (Ananas comosus L) Merr.) - Jeffary, Alicia Vanessa; Haruna, Ahmed Osumanu; Heng, Ronald Kueh jui; Lim, Liza Nuriati Kim Choo; Omar, Latifah (Canadian Center of Science and Education, 2019)
Peat soils have been developed for large scale plantations such as oil palm due to their positive contribution to Malaysia’s economic growth in agriculture sector. However, these developments contribute to the emissions of greenhouse gases (GHGs) mainly carbon (CO2) and methane (CH4). To date, there were limited information of GHGs emissions from pineapple cultivation and also inadequate data on horizontally and vertically soil GHGs emissions in peat soil profile. Thus, this study was carried out to determine carbon CO2 and CH4 emissions horizontally and vertically from a drained tropical peat soils from a drained tropical peat soils cultivated with pineapple (Ananas comosus (L.) Merr. Horizontal and vertical movements of CO2 and CH4 were measured from a drained tropical peatland with Ananas comosus (L.) Merr. Tropical peat soils cultivated with Ananas comosus (L.) Merr. contributed to 79.7 % of CO2, and 0.2 % of CH4 based on the yearly basis regardless of the differences in diurnal transportation; horizontal and vertical emission. Soil CO2 and CH4 were emitted the most through horizontal transportation with 70.84 % CO2, and 0.19 % CH4 compared to 8.85 % CO2, and 0.02 % CH4 in vertical transportation. The emission of CO2 was influenced by depth of water table and temperature. It is generally believed that lowering of peats water table leads to emission of higher CO2 emission because this process leads to exposure of peat soils to oxidation. Seasonal variation in CH4 flux was higher in the wet seasons due to rainfall; this might have increased the water table of the peat soil. The results suggest that CO2 and CH4 emissions occur both horizontally and vertically regardless of season. Therefore in order not to underestimate CO2 and CH4 emissions from peat soil, it is important to measure the emissions of this greenhouse gas which has been implicated in environmental pollution horizontally and vertically.